Pasien Laki-laki 50 tahun dengan Keratitis Oculi Sinistra di Rumah Sakit Daerah Dr. Fauziah Bireun Aceh - Saskia Hadisti Umri; Fauzan T. Banta (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2026)
Keratitis is an inflammatory condition of the cornea that may lead to permanent visual impairment if not promptly and adequately treated. It remains a significant ocular health problem, particularly in developing countries and among individuals with occupational exposure to environmental hazards. Objective: This case report aims to describe the clinical presentation, diagnostic approach, management, and prognosis of keratitis oculi sinistra in a middle-aged male patient with occupational risk factors. Methods: A descriptive case report was conducted on a 50-year-old male who presented with unilateral ocular redness, pain, tearing, photophobia, and blurred vision. Data were obtained through comprehensive anamnesis, physical examination, and detailed ophthalmologic evaluation, including visual acuity assessment and slit-lamp examination. Findings: Ophthalmologic examination revealed decreased visual acuity in the left eye, conjunctival hyperemia, ciliary injection, blepharospasm, and a grayish-white corneal infiltrate with well-defined borders, consistent with keratitis. The patient had a history of frequent exposure to dust and ultraviolet radiation due to his occupation as a fisherman and lacked the use of protective eyewear. Management included topical broad-spectrum antibiotics, topical corticosteroids, systemic analgesics, vitamin supplementation, and patient education. The clinical response was favorable, with an overall prognosis considered cautiously good. Implications: This case highlights the importance of early recognition and appropriate management of keratitis to prevent serious complications such as corneal ulceration and vision loss. Occupational eye protection, patient education, and timely treatment play crucial roles in improving clinical outcomes and preserving visual function.